Karakteristik Minuman Ready to Drink dengan Variasi Konsentrasi CMC dan Rasio Kacang Tunggak dan Kacang Hijau - Tala Desicha Amalia Mukmina; Ratih Lido Prameswari; Relita Indar Hapsari; Iffah Muflihati; Arief Rakhman Affandi (Universitas Muhammadiyah Semarang, 2019)
Indonesia is a country that is rich in natural resources and has the potential of local food from various types of beans that have the potential to add nutrients to the diet or daily menu. One of them is cowpea, which is still a lot of people have not processed the beans optimally. So as to increase the economic value and increase the variation of processed cowpea made by cowpea juice mixed with green beans (1: 3; 2: 2; 3: 1) with the addition of CMC (0.1%, 0.2%, 0.3 %) as stabilizer. The effect of CMC on green bean juice drinks and cowpea juice resulted in a descriptive test not significantly different while the preference test was found in the 1: 3 treatment with 0.1% CMC concentration. The highest total sugar is 1: 3 treatment with the addition of 0.2% CMC concentration of 10.6% while the lowest total sugar is in treatment 3: 1 addition of 0.3% CMC concentration of 4.89%. Protein levels in the treatment of 1: 3 added 0.1% CMC concentration which was equal to 5.74%.